Improved formulations of shape factors for the freezing and thawing time prediction of foods - Ilicali, Coskan; Teik, Tang Hee; Shian, Lim Phaik (Academic Press, 1999)
Improved formulations of shape factors for the freezing and thawing time of infinite cylinders, spheres and ellipses have been proposed. Finite difference models were used for data generation. The generated data were correlated by regression analysis to yield equations which expressed the shape factors as a function of the Biot number, the initial and final temperature of the food, the ambient temperature and the dimensions of the food. It was possible to predict the numerical results with absolute mean errors lower than 4.0% with the shape factor expressions proposed. © 1999 Academic Press.